Neuropsychological deficits in depression – a challenge for cognitive-behavioral therapies (Journal of Medical Science, 2019)
Neuropsychological deficits in depression are a significant therapeutic challenge. Their occurrence means poor therapeutic prospects, worse social and professional functioning after therapy, as well as a higher risk of relapse. Despite clinical improvement, they often remain even in a state of complete remission. Beck’s model of depression does not include interventions directed at neuropsychological processes leading to neurocognitive mechanisms responsible for the development and maintenance of depression. More recent trends in cognitive-behavioral therapy seem to involve neuropsychological processes to a greater extent. This applies to Well’s metacognitive model, which focuses on the meta-level of thinking. Therapeutic process involves various aspects of attention, as well as detached mindfulness. Available empirical studies indicate that this therapy model is more effective in reducing neuropsychological deficits than Beck’s model. Acceptance and commitment therapy as well as mindfulness-based cognitivetherapy both focus on the development of skills that are related to the efficiency of executive functions and flexibility of attention, i.e. the cognitive processes whose deficits are characteristic of depression. However, research is needed to confirm their effectiveness in reducing neuropsychological deficiencies compared to other therapeutic models. Interventions in the field of cognitive remediationcan be used to enrich cognitive-behavioral therapies and increase their effectiveness. Until now, they have been used as a separate form of therapy, for example in anorexia.